Biosorption of Cadmium(II) Ions from Wastewater using Carabao Grass (Paspalum conjugatum): Morphological Characterization and Adsorption Kinetic Studies - Barido, J.; Badong, V.; Zabala, G. (Asian Journal of Chemistry, 2026)
The presence of cadmium(II) in wastewater poses significant risks to human health and the environment, highlighting the need for sustainable and efficient treatment methods. This study aimed to evaluate dried powdered carabao grass as an adsorbent for cadmium by examining its morphology, adsorption capacity and the isotherm and kinetic models governing the adsorption process using a true experimental design. The morphology of the adsorbent was analysed through scanning electron microscopy (SEM), while cadmium concentrations were determined using ICP-OES. SEM images revealed that the adsorbent exhibited an irregular, elongated structure with extensive pores, which contributed to its adsorption performance. The material achieved a maximum adsorption capacity of 0.588 mg g–1 and a cadmium removal efficiency of 93.68% at a contact time of 180 min. Adsorption isotherm analysis showed high correlation coefficients for both the Langmuir (R2 = 0.9996) and Freundlich (R2 = 0.9883) models. However, the Langmuir constant (KL = -91.554 L mg–1 and Qmax = 0.513 mg L–1) and Freundlich constants (KF = 0.468 mg (L mg–1)1/n and n = -9.862) showed otherwise. This indicates that neither Langmuir nor Freundlich isotherm model are suitable in describing the adsorption of cadmium(II) ions onto the dried powdered carabao grass. Conversely, the adsorption kinetics followed pseudo-second-order kinetic model (R2 = 0.9971) which resulted to a rate constant of 0.3791 g mg–1 min–1. Thus, the dried powdered carabao grass was an ideal adsorbent of cadmium governed by chemical adsorption.